2020
DOI: 10.1002/ece3.6943
|View full text |Cite
|
Sign up to set email alerts
|

Application of leaf size and leafing intensity scaling across subtropical trees

Abstract: As the terminal part of the tree canopy, current-year shoots (i.e., twigs) sustain the static and dynamic biomechanical forces generated by leaves, flowers, and fruits (Niklas, 1992; Suzuki, 2003). At a very basic level, leaves and stems are both structurally and physiologically organographic units integrated into the context of biomass al

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…But our study showed that the LA gradually increased up to 2,500 m. This non-intuitive pattern might be caused by the influence of precipitation on LA. The lowest elevation of our plots was located in a dry valley, where plants exhibited smaller leaves ( Niinemets, 2001 ; Rudgers et al, 2019 ; Sun et al, 2020 ). As the altitude increased, precipitation and atmospheric humidity gradually increased, and LA also increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But our study showed that the LA gradually increased up to 2,500 m. This non-intuitive pattern might be caused by the influence of precipitation on LA. The lowest elevation of our plots was located in a dry valley, where plants exhibited smaller leaves ( Niinemets, 2001 ; Rudgers et al, 2019 ; Sun et al, 2020 ). As the altitude increased, precipitation and atmospheric humidity gradually increased, and LA also increased.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf mass and area are two important leaf traits for the most vascular plants. The relative changes of leaf mass and area reveal the metabolic activity and photosynthesis potential, which are not invariable ( Liu et al, 2016 ; Umaña and Swenson, 2019 ; Sun et al, 2020 ). The scaling exponent and normalization constant for LDW–LFW, LA–LFW, and LA–LDW of this study were significant positive correlations.…”
Section: Discussionmentioning
confidence: 99%
“…For trees, a shoot is a fundamental unit of growth ( Sterck et al , 2005 ; Sterck and Schieving, 2007 ; Lecigne et al , 2021 ) and reproduction ( Chen et al , 2009 ; Scott and Aarssen, 2013 ; Miranda et al , 2019 ; Fajardo et al , 2020 ). Given its importance, allometric relationships of shoot size and total shoot leaf area have been important topics in plant ecophysiology ( Corner, 1949 ; White, 1983 ; Ackerly and Donoghue, 1998 ; Brouat et al , 1998 ; Westoby and Wright, 2003 ; Kleiman and Aarssen, 2007 ; Olson et al ., 2009 , 2018 ; Sun et al ., 2010 , 2020 ; Yan et al , 2013 ; Trueba et al , 2016 ; Fan et al , 2017 ; Smith et al , 2017 ; Zhu et al , 2019 ; Fajardo et al , 2020 ). However, most previous studies on leaf vs. shoot size allometry have focused on the relationship among shoot size, total shoot leaf area, total leaf number and/or mean individual leaf size on the shoot.…”
Section: Introductionmentioning
confidence: 99%
“… Koyama et al , 2012 ; Smith et al , 2017 ), this fact was not considered in most previous studies on leaf size – shoot size allometry (e.g. Sun et al ., 2006 , 2010 , 2017 , 2019 a , b , 2020 ; Kleiman and Aarssen, 2007 ; Ogawa, 2008 ; Yang et al ., 2008 , 2009 , 2010 ; Milla, 2009 ; Xiang et al , 2009 a , 2010 ; Whitman and Aarssen, 2010 ; Dombroskie and Aarssen, 2012 ; Scott and Aarssen, 2012 , 2013 ; Yan et al , 2013 ; Dombroskie et al , 2016 ; Trueba et al , 2016 ; Olson et al , 2018 ; Miranda et al , 2019 ; Zhu et al , 2019 ; Fajardo et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The changes in leaf sizes are correlated with the availability of water and nutrients in the habitat and other plant functional traits [ 37 ]. Sun et al analyzed the twigs of 123 species datasets compiled in the subtropical mountain forest, the minimum leaf mass and maximum leaf mass versus the LI based on SM (LI), and the scaling exponents ranged from −1.24 to −1.04 [ 38 ]. Our study showed a significant negative isometric scaling relationship between ILM and LI in the three habitats.…”
Section: Discussionmentioning
confidence: 99%